THE COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE BETWEEN PT. BANK SULUTGO AND PT. BANK PAPUA YEAR 2013-2016 - Mentang, Indri Winda; Pangemanan, Sifried S.; Tumiwa, Johan . (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Banking is one of sectors that drive the economy in Indonesia. One of them is Regional Development Bank that is scattered throughout Indonesia, each have different performance based on the state of the region itself. Judging from the character of Indonesia is an agricultural country, of course, the economic character formed historically, geographical conditions also have an important role in the economy of a region. PT. Bank SulutGo and PT. Bank Papua is a Go Public bank located in eastern Indonesia. This study aims to determine the differences in financial performance between PT. Bank SulutGo and PT. Bank Papua by using RBBR method analysis. The method of this research is comparative analysis. The results show the financial performance seen from ROA there is no a significant difference, whereas if viewed from NPL, LDR, GCG, NIM, and CAR there are a significant difference. PT. Bank SulutGo and PT. Bank Papua management should not only satisfied with the results already obtained and continue to improve the company's performance in order to further increase in the future.Keywords: financial performance, regional development bank, rbbr method